Profitability as a Moderating Factor in Voluntary Sustainability Report Disclosure and Firm Value in Indonesian Non-Bank Corporations - Weli Weli; Muhammad Afif Tamin (Bina Nusantara University, 2025)
The research investigated the effect of voluntary sustainability reporting on firm value, moderated by profitability, specifically targeting Indonesian non-financial public companies. Its originality lied in examining sustainability reporting as voluntary disclosure, given that Indonesian regulations mandated it only after 2020. The research introduced a new approach by integrating moderating variables that differentiated effects at different profitability levels, where this measure was an extension of previous studies. The research also investigated whether the level of profitability affected the strength of the relationship between sustainability reporting disclosure and firm value, as measured by stock price. The sample consisted of 41 sustainability reports from non-financial public companies between 2018 and 2020, allowing the researchers to capture the impact of voluntary disclosure on firm value before the regulatory requirements. The research utilized the PROCESS Macro by Hayes in the SPSS program to analyze the data. The findings indicate that voluntary sustainability reporting disclosure positively impacts firm value, and profitability significantly moderates this relationship. Specifically, firms with lower profitability exhibit a greater positive effect of sustainability disclosure on firm value, underscoring the importance of financial performance in enhancing the impact of voluntary disclosure. These findings contribute to stakeholder theory by highlighting the role of profitability in shaping the effectiveness of sustainability reporting. The research adds to the literature by providing new insights into the strategic value of voluntary sustainability disclosure for non-financial firms, particularly those with strong financial performance, in enhancing firm value.